2021
DOI: 10.1016/j.cortex.2021.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Global motion evoked potentials in autistic and dyslexic children: A cross-syndrome approach

Abstract: Atypicalities in psychophysical thresholds for global motion processing have been reported in many neurodevelopmental conditions, including autism and dyslexia. Cross-syndrome comparisons of neural dynamics may help determine whether altered motion processing is a general marker of atypical development or condition-specific. Here, we assessed group differences in N2 peak amplitude (previously proposed as a marker of motion-specific processing) in typically developing (n = 57), autistic (n = 29) and dyslexic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Together with the results from stimulus-locked analyses using a similar dataset ( Toffoli et al, 2021 ), our results suggest that early sensory encoding of motion information is not altered in children with dyslexia. While differences in drift-rate cannot completely tease apart sensory and decision-making processes, in the current study we found no evidence of group differences in non-decision time – a measure which includes the time taken for sensory encoding.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Together with the results from stimulus-locked analyses using a similar dataset ( Toffoli et al, 2021 ), our results suggest that early sensory encoding of motion information is not altered in children with dyslexia. While differences in drift-rate cannot completely tease apart sensory and decision-making processes, in the current study we found no evidence of group differences in non-decision time – a measure which includes the time taken for sensory encoding.…”
Section: Discussionsupporting
confidence: 71%
“…These general difficulties could reflect reduced temporal and/or spatial integration of motion signals ( Benassi et al, 2010 ; Hill & Raymond, 2002 ; Raymond & Sorensen, 1998 ). This conclusion does not negate the possibility that dyslexic individuals face additional difficulties when segregating signal from noise, as we suggested based on stimulus-locked analyses using a similar dataset ( Toffoli et al, 2021 ).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…One child said that they were pressing the 'up' key if the stimulus dots were 'jumping down'. Alongside other task differences, the study by Toffoli et al (2021) lengthened the limited lifetime duration compared to Manning et al (2019Manning et al ( , 2021, which could have contributed to a smaller proportion of participants experiencing the reverse motion illusion in this later study. Notwithstanding the need for more systematic evidence, one child participant who experienced the reverse motion illusion with limited lifetime stimuli in Manning et al's (2019Manning et al's ( , 2021 study did not show this illusory percept when the lifetime was extended.…”
Section: Explanation Of the Reverse Motion Illusion In Random Dot Stimulimentioning
confidence: 96%
“…A modified version of Manning et al's (2019 , 2021 ) task was presented to typically developing children and children with an autism or dyslexia diagnosis aged between 6 and 14 years by Toffoli and colleagues ( Toffoli, Scerif, Snowling, Norcia & Manning, 2021 ). In this study, some changes were made to the task with the aim of minimizing the reverse motion illusion in children.…”
Section: New Evidence Of the Reverse Motion Illusion For Random-dot Stimuli In A Minority Of Child Observersmentioning
confidence: 99%